Percutaneous transluminal angioplasty using the novel drug-coated balloon catheter SeQuent Please NEO for the treatment of symptomatic intracranial severe stenosis: feasibility and safety study. (10th November 2018) - Gruber, Philipp; Braun, Christina; Kahles, Timo; Hlavica, Martin; Anon, Javier; Diepers, Michael; Nedeltchev, Krassen; Berberat, Jatta; Remonda, Luca
Abstract : Objectives: Intracranial arteriosclerotic disease is a relevant cause of ischemic stroke worldwide with a high recurrence rate despite best medical treatment. Following the SAMMPRIS trial, endovascular treatment has remained a second-line therapy. Meanwhile, there has been significant advances in device technology. SeQuent Please NEO is a novel polymer-free, drug-coated (paclitaxel/iopromide) balloon (DCB) primarily designed for cardiology. Because of its high flexibility and pushability, it may also be suitable for intracranial use. The aim of this study was to assess the feasibility and safety of SeQuent Please NEO DCB in symptomatic intracranial severe stenosis. Methods: A single-center retrospective cohort study of patients with symptomatic intracranial severe stenosis treated with SeQuent Please NEO DCB was performed at a tertiary stroke center. Results: Ten patients (all men, median age 73 years (IQR 69–77)) were included. Median pre-treatment stenosis grade was 78% (IQR 75–80%) with four internal carotid artery, two mid-basilar artery, and four vertebral artery lesions. Median post-treatment stenosis grade was 50% (IQR 45–53%). Successful angioplasty was achieved in all cases without technical failure. There were no cases of peri-procedural reocclusion and no deaths at median follow-up of 3 months (IQR 2–3). Conclusion: In this pilot study, SeQuent Please NEO DCB was feasible and safe in the treatment of symptomatic intracranial severe stenosis. It might represent a promising alternative to medical treatment in selected cases.